Power Factor Improvement of Buck-Boost AC-DC Converter using Pulse Width Modulation Strategy - Rajalakshmi, G; Kumar, Ashok R; Asokan, K (International Journal of Computer Sciences and Engineering, 2025)
In power electronics converters applications, the input current to the converter contains a harmonic current which leads to the low power factor. The paper attempts to develop a pulse width modulation (PWM) strategy with a view to improve the input power factor of a buck boost ac-dc converter. The difficulties in the choice of corner frequencies for filter circuits emphasize a resurgent focus on the boundaries of PWM approaches and arbitrate to traverse a fresh direction for enjoying its benefits. The theory relates to the use of two level saw tooth carrier to arrive at the appropriate pulses for both the switches. The philosophy manifests to reshape the input current waveform in an effort to phase align the same with the supply voltage. The scope travels to examine the performance of the methodology using MATLAB based simulation and involve the use of an experimental prototype to validate the results and there from establish its suitability for use in the practical world